Perinatal outcomes and long-term offspring cardiovascular morbidity of women with congenital heart disease. (March 2020) - Chilikov, Anastasia; Wainstock, Tamar; Sheiner, Eyal; Pariente, Gali
Highlights: Maternal congenital heart disease was previously shown to influence perinatal outcomes. We aimed to determine if affects cardiovascular morbidity of the offspring. We found that maternal congenital heart disease is associated with increased risk for low birth weight and cesarean delivery. The risk of long-term cardiovascular morbidity is not increased among offspring of women with congenital heart disease. Further research is required to investigate the incidence of obesity, diabetes and cardiovascular morbidity later in life. Abstract: Objective: Due to advances in medical care available for patients with congenital heart disease, these patients now have a longer life span. As a result, the number of pregnancies of mothers with congenital heart disease has increased. The purpose of the current study was to evaluate perinatal outcomes of women with congenital heart disease and to examine long-term cardiovascular morbidity of offspring to mothers with congenital heart disease. Materials and methods: A population-based cohort analysis was performed including all singleton deliveries occurring between years 1991–2014 at Soroka University Medical Center. The primary exposure was defined as maternal congenital heart disease. Short-term perinatal outcomes as well as long-term cardiovascular related hospitalizations of the offspring up to the age of 18 years were compared between women with and without congenital heart disease. To compare perinatal outcomes between the two study groups, we conducted a Generalized Estimation Equation (GEE) model accounting for maternal age and multiple occurrence in the cohort, parity, fertility treatment, smoking and induction of labor. To compare cumulative long-term cardiovascular morbidity, we compared cardiovascular hospitalization incidence of offspring of mothers with and without congenital heart disease using Kaplan-Meier survival curve and Weibull regression analysis to control for maternal age, diabetes, smoking, hypertension, birth weight, and cesarean delivery. Results: During the study period 243, 313 deliveries met the inclusion criteria, of which 369 were of mothers with congenital heart disease. Maternal congenital heart disease was found to be an independent risk factor for low birth weight (adjusted OR = 1.5 CI 95 % 1.06–2.32, p=0.022) and cesarean delivery (adjusted OR = 1.4 CI 95 % 1.09–1.86, p = 0.008). Mothers with congenital heart disease also had higher risk for placental abruption, but it was not statistically significant (adjusted OR = 2.3 CI 95 % 0.87–6.16, p = 0.09). Long-term cardiovascular morbidity was comparable between the groups (Log rank p = 0.251; adjusted HR = 1.6 CI 95 % 0.62–4.42, p = 0.313). Conclusion: In conclusion, pregnancies of women with congenital heart disease are at an increased risk for adverse short-term perinatal outcomes, such as low birth weight and cesarean delivery. However, we did not find an increase in long-term cardiovascular morbidity among offspring of these women; still this association cannot be ruled out.